Synthesis, characterization, electrochemical and spectroelectrochemical properties of novel peripherally tetra-1,2,4-triazole substituted phthalocyanines - KOCA, ATIF (ELSEVIER SCIENCE SA, 2016)
The synthesis and characterization of novel 1,2,4-triazole derivative (3), nitrile compound (5) and peripherally tetra 1,2,4-triazole substituted metal-free (6), zinc(II) (7), nickel(II) (8), cobalt(II) (7), lead(II) (9) and copper(II) (10) phthalocyanines were accomplished for the first time. Electrochemical characterization of the complexes were carried out in solution with voltammetric and in situ spectroelectrochemical measurements in different electrolytic systems. Phthalocyanines having redox inactive centers (H+, Zn+2, Cu+2, and Ni+2) illustrated similar phthalocyanine based electron transfer processes. Redox peaks of these complexes shift slightly due to the different effective nuclear charge of the ions in the core of phthalocyanine ring. The easiest reducible one is the metal free phthalocyanine due to the highest effective nuclear charge of H+. Although big size of ion in the core of lead(II) phthalocyanine disturbed the square planar structure of the complex, this phenomena did not considerably influence the redox processes of lead(II) phthalocyanine. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Synthesis; Phthalocyanine; 1,2,4-triazole; Electrochemistry; Spectroelectrochemistry; METAL-FREE; PHOTOCHEMICAL PROPERTIES; CATALYTIC-ACTIVITY; ZINC; METALLOPHTHALOCYANINES; SURFACE; ELECTROSORPTION; DEMETALATION; DERIVATIVES; MANGANESE